The mixed mode analysis of arbitrary configuration of cracks in an orthotropic FGM strip using the distributed edge dislocations. (January 2018) - Monfared, M.M.; Bagheri, R.; Yaghoubi, R.
Abstract: The mixed mode fracture behavior of a functionally graded orthotropic strip based on the distribution of dislocations is studied. Fourier transform is employed to construct a system of Cauchy-type singular integral equations. These equations are solved numerically using the Lobatto–Chebyshev integration formula for the density of dislocations on a crack face. The technique allows for modeling of arbitrary crack configurations. The effects of the material constants, non-homogeneity parameter and several different cases of crack configurations on the SIFs are studied.